Backward-tracking simulations of sea ice in the Sea of Okhotsk toward understanding of material transport through sea ice - Kuga, Mizuki; Ohshima, Kay I.; Kishi, Sachiko; Kimura, Noriaki; Toyota, Takenobu; Nishioka, Jun (Journal of oceanography, 2024)
Material transport by sea ice plays an important role in the biological production of spring blooms. We conducted backward-tracking simulations to estimate the origins of the sea ice in the southern part of the Sea of Okhotsk and examine the relationship between the origin of sea ice and biological production, the concentration of iron, and the frazil ice fraction. The simulation of the sea ice melted in areas, where the net community production (NCP) was estimated shows that the sea ice that melted in areas with high NCP tended to originate in coastal areas, mostly the Terpenia Bay and Sakhalin polynyas, where ice production is high and sea ice can incorporate the seafloor sediments. This result supports the hypothesis that the incorporation of sedimentary particles into sea ice and their release during ice melt are key factors in high biological production. The simulation of the sea ice floes sampled by the icebreaker Soya off Hokkaido coast suggests that the samples collected over the shelf with depths of less than 500 m or so were formed over the shelf around the southern tip of Sakhalin Island, whereas the samples, including that with high iron concentration, collected over the shelf slope at greater depths were likely transported from the northern area up to Terpenia Bay but not further north. The simulation also suggests that the sea ice floes with a high fraction of frazil ice could be formed anywhere in the southern part of the Sea of Okhotsk.